Role of Postoperative Antimicrobials in Cleft Palate Surgery. Issue 1 (July 2015) - Aznar, María Luisa; Schönmeyr, Bjorn; Echaniz, Gastón; Nebeker, Lismore; Wendby, Lisa; Campbell, Alex
<x xml:space="preserve">Abstract</x> Background: The purpose of this study was to determine whether administration of postoperative antibiotics affects the incidence of complications after primary cleft palate repair in a developing area. Methods: This study was a prospective, double-blind, randomized, placebo-controlled trial composed of 518 consecutive patients who underwent primary cleft palate repair at a single institution. Patients were aged 1 to 43 years at the time of surgery (median, 9 years). The patients were divided randomly into two groups. One group received a 5-day regimen of oral amoxicillin (50 mg/kg/day) postoperatively and the other group received placebo medication. Both groups received a single dose of cefuroxime (30 mg/kg) before incision. Patients and providers were blinded to the randomization. Patients were followed postoperatively for early complications (infection and wound breakdown) and for late complications (palatal fistulas). Results: The incidence of early complications was 13.8 percent among the patients in the placebo group and 8.7 percent among the patients in the antibiotic group (p = 0.175). Fistulas were noted in 17.1 percent in the placebo group and in 10.7 percent in the antibiotic group (p = 0.085). Logistic regression analysis identified visiting surgeons as the only covariate related to early complications (OR, 3.71; p < 0.001). However, the use of placebo (OR, 2.09; p = 0.037), female sex (OR, 2.04; p = 0.047), and Veau III and IV (OR, 3.31; p = 0.004) were observed as factors associated with the incidence of fistulas. Conclusion: The authors' results indicate that postoperative antibiotic prophylaxis can reduce the incidence of fistulas after primary cleft palate repair in a developing area.